The Relationship Between Knowledge Level and Professional Students' Attitudes Towards Occupational Health and Safety (K3) in The Operating Room - Taebenu, Fiyola; Elon, Yunus (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Occupational Health and Safety refers to a safe and healthy workplace situation for workers, the company, and the community and environment in the factory or worksite area. Injuries from accidents are the most frequently reported physical risks in the operating room. This study aims to determine the relationship between the knowledge and attitudes of professional students of the Faculty of Nursing, Adventist University of Indonesia regarding (K3) in the operating room. The type of research used in this study is correlation analysis with a cross-sectional approach. Data analysis was carried out using 2 methods, namely Univariate Analysis and Bivariate Analysis using Spearman Rho. The results of the study found that the level of knowledge of professional students regarding K3 in the operating room is still relatively low. Most respondents have knowledge in the category of less (91.8%) and have a less good attitude (55.1%), while only a small portion showed a good or very good attitude. Professional students' attitudes and understanding about K3 in the operating room are significantly correlated negatively. A substantial but negative link is found, as indicated by the Spearman Rank correlation test value of r = -0.640 with p = 0.000. This implies that a better attitude does not always follow from greater knowledge. The conclusion of the study shows that professional students of the Faculty of Nursing, Adventist University of Indonesia do not yet have clear attitudes and knowledge about (K3) in the operating room.